Polisemantic Character of Phraseologisms in English and Uzbek Languages (Eurasian Research Bulletin, 2022)
English translation of Uzbek word-length dictionaries provides information about their phraseological features. The article focuses on the basics of grammar in the English language and the information on the polysemic meaning of words in them.